Clonal relationship in multisited mucosa‐associated lymphoid tissue lymphomas: a single‐centre experience. (23rd May 2020) - Condom, Maria; Climent, Fina; Fernández, Davinia; Colomer, Dolors; Lopez‐Guerra, Mónica; Varela, Mar; Carro, Itziar; Maluquer, Clara; Mercadal, Santiago; Oliveira, Ana Carla; Pané, Maria; Matias‐Guiu, Xavier; et al.
Summary: Clonal heterogeneity in multisited or recurrent lymphoid neoplasms is a phenomenon that has been increasingly studied in recent years. However, in mucosa‐associated lymphoid tissue (MALT) lymphomas it remains largely unexplored. Patients diagnosed at our institution with multisited MALT lymphoma, from January 2009 to October 2018, were studied. Molecular studies were performed for the detection of clonally rearranged immunoglobulin by polymerase chain reaction.In all, 91 patients were included. Of those, 28 had a multisited disease and in 16 clonality studies were done. In eight cases, multifocal involvement was synchronous and in eight metachronous. Patients with non‐gastric gastrointestinal tract involvement tended to disseminate within the same tract, without observing other specific dissemination patterns. Four cases (25%) had clonal heterogeneity at the different organs involved. All patients with late relapses (two patients) had different clones. The majority of patients with multisited MALT lymphomas presented with the same clone in the different involved organs, identifying a different clone in those with late relapses. These patients could represent de novo neoplasms, rather than a relapse. This could mean that some individuals might have a genetic predisposition to develop this type of lymphoma and it could also have clinical implications regarding therapeutic decisions.